Lords of the land and black settlers in Piura and Querecotillo. Notes about freedom struggles and civil rights in the republic birth process between 1825-1855 - Espinoza Claudio, César (2019)
In this research we progress towards a more specific understanding about republican slavery forms, social resistance experiences of the slaved and freed black population, and practice of the abolitionist system carried out in a situation of building up the republic in a regional space: the province of Piura. Through case studies, we examine the path that afro-descendants assumed using laws and social force of their representatives in the courts to destroy the chains that oppressed them under the new creole republic. We review liberations through purchase, sell, and master’s grace, but also other forms of freedom conquest as the banditry social movement in a independence war context. Likewise, we present and examine the political experience that will be lived by popular castes settled within Tangarará’s latifundia, and political resistance to the elimination project of the Querecotillo town led by the army colonel Don Francisco Xavier Fernández de Paredes.